Dear Mx. Ortiz – Compressed - Schriefer, Natalie (2021)
Keywords: dept.hhs

Flash Fiction: How to Build a Pyramid Fire in the Rain by Natalie Schriefer - Schriefer, Natalie (JMWW, 2021)
Do not walk away from this burgeoning hope of heat and dryness.
Keywords: dept.hhs

The Complicated Process of Rejecting Heteronormativity | Dame Magazine - Schriefer, Natalie (Dame Magazine, 2021)
For 25 years, I thought I was a great proponent of LGBTQ+ rights. I supported queer friends and acquaintances; I stayed up to date on terms and phrasing; I asked for gender pronouns; I went to Pride. So when I had my first same-sex crush, I thought my transition from ally to community member would
Keywords: dept.hhs

The English Teacher Who Taught Me How to Hear - Schriefer, Natalie (The Wisdom Daily, 2021)
Have you listened to yourself recently?
Keywords: dept.hhs

The Complicated Queerness in Breath of the Wild - Schriefer, Natalie (Medium, 2021)
Let’s talk about Bolson and Vilia. CW: Transphobia
Keywords: dept.hhs